Parametric study of solid-solid translucent phase change materials in building windows. (1st November 2021) - Gao, Yuan; Zheng, Qiye; Jonsson, Jacob C.; Lubner, Sean; Curcija, Charlie; Fernandes, Luis; Kaur, Sumanjeet; Kohler, Christian
Graphical abstract: Highlights: Developed EnergyPlus compatible equivalent models for PCM windows. Optimal PCM windows save 17.2% HVAC energy in warm climates. Energy savings are sensitive to solar absorptance of PCM the most. Optimal central phase change temperatures are determined for three climates. PCM windows shift the peak loads in buildings. Abstract: Thermal energy storage and solar radiation management are crucial to improve the sustainability and energy efficiency of buildings. Compared with the implementation of phase change materials (PCMs) in opaque components, the energy saving potential of incorporating PCMs in transparent glazing windows is much less studied and not well understood. Here we present a comprehensive parametric study of novel PCM windows for building energy saving with a focus on optimizing and quantitatively distinguishing the contributions from the optical and thermal properties of the PCM, which is particularly useful for the design of solid-solid PCM windows. We investigate a reference commercial office building using EnergyPlus by developing an equivalent model of our PCM window that is compatible with EnergyPlus's modeling capabilities. Compared with a clear-clear double-pane window, the integration of 3 mm solid-solid PCMs with optimal properties in warm, mixed, and cold climates can respectively save up to 17.2%, 14.0%, and 5.8% energy for the HVAC (heating, ventilation, and air conditioning) system, and 9.4%, 6.7%, and 3.2% energy for the whole building. We also demonstrate that these energy savings are most sensitive to the solar absorptance of PCMs for all three climates. The optimal transition temperature varies with climate and is related to the climate and solar radiation heat gain. Other issues are also briefly discussed, such as hysteresis, window orientations, and the effect of interior lighting. Although the optimal PCM windows show energy saving performance comparable with low-emissivity windows, the PCM windows provide a unique advantage in terms of shifting HVAC loads which can provide benefits to the electrical grid.